Consumption of Ashtanga Ghrita (clarified cow butter added with herb extracts) improves cognitive dysfunction induced by scopolamine in rats via regulation of acetylcholinesterase activity and oxidative stress - Sharma V.; Firdaus Z.; Rai H.; Nayak P.K.; Singh T.D.; Gautam D.N.S. (My University, 2025)
Objectives: Ashtanga Ghrita (AG), an Indian traditional formulation, has been used to promote neuropharmacological activities. AG is made up of clarified cow butter (ghee) and eight different herbs. Methods: To test whether scopolamine (SCP)-induced dementia and brain oxidative stress can be counteracted by AG, rats were separated into five groups (n=6/group): Group one control, group two SCP (1 mg/kg b.w., i.p.) treated and group three to five were co-treated with different doses of AG (1.25, 2.5 and 5 g/kg b.w., orally) and SCP. After the treatment regimen, behavioral (Y-maze test) and brain biochemical changes were measured in all groups. Results: Microbial load and heavy metals were found within permissible limits. Results from attenuated total reflection Fourier-transform infrared spectroscopy demonstrated the complexation/interaction of herbal phytoconstituents with the functional groups of Ghrita. Preliminary phytochemical analysis of AG exhibited the occurrence of flavonoids, phenolics, glycosides, steroids, triterpenes, tannins, and amino acids. Findings of the experimental study exhibited that AG significantly protected the rats from SCP-induced behavioral dysfunction and brain biochemical alterations. Conclusions: This study demonstrates that AG protects the brain from SCP-induced dementia by promoting brain antioxidant activity and thus could be a promising drug for the treatment of neurodegenerative disease. © 2021 Walter de Gruyter GmbH, Berlin/Boston.